2004
DOI: 10.1242/dev.01178
|View full text |Cite
|
Sign up to set email alerts
|

Determination of embryonic polarity in a regulative system: evidence for endogenous inhibitors acting sequentially during primitive streak formation in the chick embryo

Abstract: Avian embryos have a remarkable capacity to regulate: when a pre-primitive streak stage embryo is cut into fragments, each fragment can spontaneously initiate formation of a complete embryonic axis. We investigate the signalling pathways that initiate primitive streak formation and the mechanisms that ensure that only a single axis normally forms. As reported previously, an ectopic primitive streak can be induced by misexpression of Vg1 in the marginal zone. We now show that Vg1 induces an inhibitor that trave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 81 publications
4
88
0
2
Order By: Relevance
“…This suggested that there must be a control mechanism which contributes to the formation of a polarized axis and also inhibits the tendencies of other regions to initiate an axis. These reports support the notion that a region responsible for axis initiation exists at the posterior side of the area pellucida (Spratt and Haas, 1960;Spratt, 1963;Khaner and Eyal-Giladi, 1986;Khaner and Eyal-Giladi, 1989;Khaner, 1993;Khaner, 1998, Bertocchini et al, 2004. Moreover, it was found that the midline region of the avian blastoderm has a crucial role in the process of axis formation (Khaner, 1996).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…This suggested that there must be a control mechanism which contributes to the formation of a polarized axis and also inhibits the tendencies of other regions to initiate an axis. These reports support the notion that a region responsible for axis initiation exists at the posterior side of the area pellucida (Spratt and Haas, 1960;Spratt, 1963;Khaner and Eyal-Giladi, 1986;Khaner and Eyal-Giladi, 1989;Khaner, 1993;Khaner, 1998, Bertocchini et al, 2004. Moreover, it was found that the midline region of the avian blastoderm has a crucial role in the process of axis formation (Khaner, 1996).…”
Section: Discussionsupporting
confidence: 75%
“…A recent publication indicated that Vg1 induces an inhibitor that travels across the embryo (3mm distance) in less than 6 hours (Bertocchini et al, 2004). Although such inhibitors exist, they could not prevent the initiation of more than one embryonic axis (series Aa, Ba and Db).…”
Section: What Is the Meaning Of Inhibition If Two Or Even Three Axes mentioning
confidence: 99%
See 2 more Smart Citations
“…When the chicken egg is laid, the embryo, which already contains about 50,000 cells and is organised in a flat round single‐layered blastodisc (epiblast) can be cut in pie‐shaped slices, and each slice can generate an embryonic axis 62, 63, 64, 65, 66. This property lasts until the initiation of gastrulation, 12 hours after the egg has been laid, when a lower extra‐embryonic layer has grown below the epiblast and the embryonic axis, or primitive streak, is about to appear.…”
Section: A Historical Perspective On Avian Pgcs: Is Maternal Specificmentioning
confidence: 99%